Declining North American snow cover ablation frequency. (9th April 2021) - Suriano, Zachary J.; Leathers, Daniel J.; Mote, Thomas L.; Henderson, Gina R.; Estilow, Thomas W.; Wachowicz, Lori J.; Robinson, David A.
Abstract: At a continental scale, trends in aggregate ablation frequency inform changes in snow cover extent, however the variability and trends in the frequency and magnitude of snow ablation events at regional scales are less well understood. Determining such variability is critical in describing regional hydroclimate, where snow ablation can influence streamflow, soil moisture and groundwater supplies. This study uses a gridded dataset of United States and Canadian snow ablation events derived from 1960 to 2009 surface observations to examine spatial and temporal variations of snow ablation frequency. Here, we show a relatively narrow band of peak ablation frequency seasonally advances and recedes over North America, forced by variations in snow depth and meteorological conditions suitable for ablation. Particularly in more moist regions away from the continent's interior, hydrologically relevant ablation events of at least 10.0 cm occur on an approximately yearly basis. Collectively, ablation events became significantly less frequent with time, where events specifically in the Appalachians and in Great Lakes regions declined by as much as 75% over the 50‐year period. Decreases in ablation frequency across the study region are primarily driven by significant decreases in snow cover, inhibiting the potential for ablation to occur due to a lack of sufficiently deep snowpacks. These results point to important snow cover related changes in the hydrologic cycle in a warming climate and highlight specific areas of interest where more localized analysis of ablation trends and forcing mechanisms would be appropriate. Abstract : The interannual frequency of snow cover ablation events over North American is significantly related to the quantity of snowfall received during the cold season, in relation to warming atmospheric temperatures. From 1960 to 2009, the frequency of such ablation events has significantly changed across the continent, shown here, with fewer events occurring in the Appalachians, north of the Great Lakes and along the front range in Montana with time.